Current Trends in Prevalence and Role of Long Noncoding RNA and Gene Fusion in Prostate Cancer: An Overview - Arun Sinha; Praveen Sharma; Kamla Kant Shukla; Prasenjit Mitra; Sanjeev Misra (Annals of the National Academy of Medical Sciences (India), 2021)
Objectives The aim of this study is to analyze the current scenario in the diagnostic modalities for prostate cancer. Materials and Methods We searched PubMed, Google Scholar, and ResearchGate for relevant data. Articles published in the last 10 years were taken into consideration. The role of long noncoding RNA and gene fusion products in the context of prostate cancer was reviewed, which included their roles in diagnosis, prognosis, and assessment of response to therapy. Results Several long noncoding RNAs (lncRNA) have been isolated and have been shown to be useful in diagnosing and prognosticating prostate cancer. We have also looked into the role of TMPRSS2:ERG gene fusion in prostate carcinoma diagnosis. These molecular parameters have been looked into due to the fact that the current parameters in use such as prostate-specific antigen have several drawbacks that limit their potential.